Usability Effectiveness of the State Polytechnic of Malang’s Learning Management System as e-Learning Media - Nadia Layra Aziza; Shelyca Surrayensih; Tita Wijayanti; Arwin Datumaya Wahyudi Sumari (Institut Teknologi Dirgantara Adisutjipto, 2023)
The rapid development of information technology has impacted the education sector by supporting a more efficient and effective learning process. During the Covid-19 pandemic, online learning through e-Learning flourished and encouraged the transformation of conventional education to digital form, one of which is the Learning Management System (LMS). This research is aimed to carry out a deep analysis of its utilization as a learning media and the influencing factors of its utilization to determine the level of its usage effectiveness at the State Polytechnic of Malang. This research uses a quantitative descriptive method with a questionnaire as the research instrument for collecting data. The research uses System Usability Scale (SUS) evaluation method for determining scenarios, selecting respondents, collecting data, and performing calculations. The overall measurement results show that the SUS assessment score is 54.67, with a Learn ability, Efficiency, and Memorability aspect score of 33.61. Then the Errors aspect score is 21.06, while the Satisfaction aspect score is 12.77. The LMS at the State Polytechnic of Malang has a low usability value, with a description Acceptability of Marginal, Grade Scale of D, and Adjective Rating of OK. Based on the final SUS score, the level of usage effectiveness of State Polytechnic of Malang’s LMS is still relatively low. However, its utilization is still accepted but needs improvement in some aspects.